Chorionic Villus Sampling in Assisted Versus Spontaneous Conception Twins - Daskalakis, Georgios; Antsaklis, Panagiotis; Gourounti, Kleanthi; Theodora, Mariana; Sindos, Michail; Papantoniou, Nikolaos; Loutradis, Dimitrios (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose To compare the outcome of chorionic villus sampling (CVS) in twin pregnancies following assisted reproduction technology (ART) versus twins that have been conceived spontaneously.Materials and Methods Retrospective analysis of dichorionic twin pregnancies that underwent CVS between 1986 and 2013 at our department which is a tertiary center for fetal medicine. 32 twin pregnancies after ART and 130 spontaneously conceived twin pregnancies, which underwent CVS, were analyzed.Results No difference was observed in the pregnancy loss rate between the two groups (0 % in the ART group vs. 3 % in the spontaneous twins group). The rate of preterm delivery before 28 weeks was higher in the ART group (18.8 %) compared to the control group (1.6 %). The perinatal mortality rate was similar in the two groups.Conclusion The pregnancy loss rate following CVS is similar in ART twins and in spontaneous twins. However, the risk of prematurity before 28 weeks is significantly higher in the ART group.
Keywords: interventional procedures; ultrasound; obstetrics; twins; chorionic villus sampling